Determining location models for offline Micro-Entrepreneurs in Sabah using personal decision support systems - Esmadi Abu Abu Seman; Syed Nasirin Syed Zainol Abidin; Suddin Lada; Tamrin Amboala; Carolyn Salimun; Noor Hassanah Husin; Suraya Miskon (Association for Computing Machinery, 2025)
Selecting proper site is a significant challenge for offline microentrepreneurs in Sabah, where socio-economic factors complicate decision-making and intuition-based approaches often lead to financial losses. This paper proposes a Personal Decision Support System (PDSS) framework that integrates location models to guide informed site selection decisions. A mixed-methods approach, including interviews, observations, and archival research, was used for data collection. Key findings show that PDSS reduces the risk of poor location decisions and boosts profitability by replacing subjective judgment.